IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN FIQIH - Taufik Qurrahman; Wasith Achadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract The purpose of this research is to analyze the implementation of the independent curriculum at MI Assalam Srigunung. With this type of qualitative research with a phenomenological approach. The location of this research was conducted at MI Assalam Srigunung. The source of this research data is the informant. With the research subject 1 homeroom teacher. The collection of technical data through observation, interviews and documentation, the results of this study show that the implementation of the Merdeka curriculum at MI Assalam Srigunung madrasah has not been fully implemented. Because there has been no follow-up from the Ministry of Religion. The school also had its own initiative to create the Merdeka curriculum training and also learned from several elementary school teachers who had implemented the Merdeka curriculum